2019
DOI: 10.3892/ol.2019.10903
|View full text |Cite
|
Sign up to set email alerts
|

PD‑L1 expression levels on tumor cells affect their immunosuppressive activity

Abstract: Programmed cell death 1 (PD-1) is an immuno-checkpoint receptor which is primarily expressed on T cells, monocytes, natural killer cells and macrophages. Programmed death-ligand 1 (PD-L1) is the primary ligand of PD-1 and is constitutively expressed on antigen presenting cells, mesenchymal stem cells and bone marrow-derived mast cells. In addition, PD-L1 is also expressed on a wide range of tumor cells, including lung cancer, breast cancer and melanoma. PD-1 and PD-L1 are important members of the immunoglobuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 50 publications
(52 reference statements)
3
65
0
Order By: Relevance
“…Although many immortalized cell lines may have a reduced HLA expression [ 65 , 66 , 67 ], it is conceivable that some cancer cells induce an HLA mismatch when co-incubated with hPBMCs, being from different donors. However, in line with other similar papers published in the literature [ 61 , 62 , 63 , 64 ], for all tested combinations (in our case controls and treatments with ipilimumab under high glucose and low glucose) the differences between groups are still due to the treatment conditions. Moreover, different open discussion papers are available about the role, for example, of HLA-E in co-cultures of cancer cells and PBMCs [ 68 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although many immortalized cell lines may have a reduced HLA expression [ 65 , 66 , 67 ], it is conceivable that some cancer cells induce an HLA mismatch when co-incubated with hPBMCs, being from different donors. However, in line with other similar papers published in the literature [ 61 , 62 , 63 , 64 ], for all tested combinations (in our case controls and treatments with ipilimumab under high glucose and low glucose) the differences between groups are still due to the treatment conditions. Moreover, different open discussion papers are available about the role, for example, of HLA-E in co-cultures of cancer cells and PBMCs [ 68 ].…”
Section: Discussionsupporting
confidence: 88%
“…There are some limitations of this study: firstly, human leukocyte antigen (HLA)-class I molecules on tumor cells have been regarded as crucial sites where cytotoxic T lymphocytes can recognize tumor-specific antigens. HLA mismatch could be a possible limitation of co-cultures of tumor cells with hPMBCs, despite co-culture models often being used and recommended in preliminary cell-lymphocytes interaction studies, as reported in the literature [ 61 , 62 , 63 , 64 ]. Although many immortalized cell lines may have a reduced HLA expression [ 65 , 66 , 67 ], it is conceivable that some cancer cells induce an HLA mismatch when co-incubated with hPBMCs, being from different donors.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1, the primary ligand of PD-1, is expressed in several cancer cells, including those of the breast [40,41]. Thus, we investigated whether the ablation of ObR may also modulate PD-L1 expression in all employed experimental models.…”
Section: Leptin Receptor Knockdown Affects the Breast Tumor Immune MImentioning
confidence: 99%
“…One of the defense mechanisms used by cancer cells is activation of PD‐L1 receptor in the tumor environment, which causes suppression of immune cells. PD‐L1 or PD‐L2 may be present on cancer cells, mesenchymal stromal cells, and antigen presenting cells (APCs) 6 . Tumor infiltrated T cells (TILs) may undergo elimination via apoptosis or remain in anergy leading to exhaustion due to the interaction of the PD‐1 molecule present on their surface with PD‐L1 or PD‐L2 ligands found on cancer cells and APCs (Figure 3a).…”
Section: Pd‐1/pd‐l1 Checkpoint Inhibitors Principlesmentioning
confidence: 99%